Dual catalysis for enantioselective convergent synthesis of enantiopure vicinal amino alcohols - Chen-Xi Ye (Nature Portfolio, 2018)
Chiral vicinal amino alcohols are found in many bioactive compounds and may serve as chiral ligands. Here, the authors report a photocatalytic enantioselective cross-coupling of nitrones with aromatic aldehydes with a chiral ligand-coordinated rare earth ion synergistically producing enantiopure vicinal amino alcohols.